Real food fermentation : preserving whole fresh food with live cultures in your home kitchen - Lewin, Alex (Quarry Books, 2012)
"Learn how to choose and prepare only the best, freshest ingredients for all your kitchen fermenting projects with Real Food Fermentation!* Learn how to make tasty foods including kimchi, yogurt, and sauerkraut* Improves digestion* Enzyme-rich foods contain high nutrient value* Boosts "good" bacteria productionFermentation is one of the earliest forms of natural food preservation, and without it, our beloved vegetables, fruits, grains, and milk would be heaps of moldy abundance after the harvest. Learn how to turn simple ingredients into health goldmines such as kimchi, sauerkraut, kefir, kombucha, and more in this flavorful book. Author and health strategist Alex Lewin empowers you with the tools, techniques, instructions, and delicious recipes to make all fermented foods at home in this essential book for your culinary library. Inside, you'll find recipes for making coleslaws, preserved lemons, ceviche, vinegars, yogurt, and more. The science, art, and craft of fermenting foods are also explained in meaningful detail"--